Education on the DASH Diet as a Comprehensive Nutritional Approach to Hypertension Management in the Coastal Region of Atowatu - Nofitasari, Ari; Purnamasari, Anisa; Saranani, Selpirahmawati; Andriani, Rina; Apriawal, Jabal (Nursing Genius Journal, 2025)
Background: Hypertension is one of the leading causes of morbidity and mortality in Indonesia. Public knowledge regarding hypertension management in coastal areas remains limited, as coastal communities generally consume high-salt diets due to the frequent intake of salted fish and processed seafood products. Objectives: This study aimed to examine the effect of DASH (Dietary Approaches to Stop Hypertension) diet education as an integrated nutritional approach to hypertension control in coastal areas. Methods: This study employed a quantitative approach with a quasi-experimental design using a pretest–posttest without a control group. The research was conducted in the coastal area of Atowatu Village, Soropia District. The study population consisted of individuals with mild to moderate hypertension residing in the coastal area of Atowatu Village, Soropia District. A total of 70 participants were selected through purposive sampling based on inclusion and exclusion criteria. Results: Prior to the intervention, 48 respondents (68.6%) had poor knowledge, while 22 respondents (31.4%) had moderate knowledge. After the educational intervention, 1 respondent (1.4%) had poor knowledge, 62 respondents (88.6%) had moderate knowledge, and 7 respondents (10%) demonstrated good knowledge. Regarding hypertension categories, before DASH diet education, 38 respondents (54.3%) were classified as having severe hypertension. Following the intervention, the majority of respondents were classified as having mild hypertension (48 respondents; 68.8%). Conclusion: There was a statistically significant difference in knowledge levels before and after the DASH diet education (p = 0.000), indicating that DASH diet education as an integrated nutritional approach significantly influenced hypertension control in the coastal area of Atowatu.